Labour Market Restructuring and the Nature of Employment Relations in Nigeria - Ikeije, Ugochukwu U. (Journal of Technology Management and Business, 2020)
The Nigerian labour market has experienced remarkable structural changes in the last two decades following the dictates of globalisation. These changes manifested in the sectoral composition of employment, growth in the service and informal sectors, increased youth unemployment, increased self-employment, and growth in female labour participation. These developments equally affected employment arrangement by shifting attention from the traditional employment arrangement characterised by full-time permanent employment to a more flexible employment arrangement and non-standard jobs. This paper examined the emerging structural changes in the labour market and their consequences for employment relations in Nigeria. The paper adopted desk review methodology which involved analysis of secondary data from relevant research institutions, government agencies and corporate organisations. Evidence from the secondary data revealed that Nigeria has witnessed increased youth unemployment and underemployment, the decline in full-time permanent jobs, rise in casual/contract and part-time work, rise in female labour participation, rise in outsourcing and increase in labour shedding in the last two decades. The observed implications of these developments for employment relations include a decline in union density and bargaining power; a gradual increase in non-union representation; a shift in skill requirement; emphasis on employee loyalty and commitment; emphasis on work-life balance and flexible working hours. The paper, therefore, concludes that structural changes in the Nigerian labour market have affected traditional institutionalised employment relations, which are gradually being replaced by flexible and individualised employment relations.